Innovation Model of Creative Tourism Route Management with Participation of Chaiyaphum Province - Doungmala, Dr.Thudsanaiyawan; Phutcharinya, Dr.Annarviya; Chaisri, Dr. Anchalee (Journal for Developing the Social and Community, 2018)
The objectives of this research were (1) to study the potential and the need for participant participation in the development of creative tourism management in Chaiyaphum Province; and (2) to create an innovative model of creative tourism route management with participation of chaiyaphum province. Quantitative and qualitative methods were applied in this research. The population of this research were stakeholders in tourism, Chaiyaphum province. Four hundred of stakeholders in tourism were selected by using quota sampling technique and collected data by using questionnaire. Stakeholders in tourism were selected by using purposive sampling and collected the qualitative data by using focus group. Quantitative data was analyzed by using percentage and mean, qualitative data was analyzed by using content analysis. The research results were as follows: (1) Overview Potential of stakeholders in tourism at the moderate level. (2) Overview demand for the participation of the Party tour on a high level. (3) Innovative model of creative tourism route management with participation of Chaiyaphum province are IPAC; consists of I: Information, P: Preparation, A : Action, and C: Conclusion